TEM Examination of Surface Characteristics of Rubberwood (Hevea brasiliensis) HTMP Fibers - Singh, A.P.; Yoon, Soo Kim; Gap, Chae Chung; Byung, Dae Park; Wong, Andrew H.H (Walter de Gruyter, 2003)
A study was conducted on the surface features of rubberwood high temperature thermomechanical (HTMP) fibers. The transmission electron microscopy (TEM) was used for the characterization of the surface features. The fracture behavior of the cell walls of the fibers were also studied. It was found that the outer surface of the HTMP fiber wall was completely covered by middle lamella, whose thickness was highly variable.